Norma z artykułu 38 Konstytucji RP z 1997 r. jako zasada prawa: [Norm of law in Art. 38 of the Poland’s 1997 Constitution as principle of law] (Studia Prawnicze / The Legal Studies, 2006)
Normom konstytucyjnym przypisuje się z reguły równy status, przyjęło się jednak wyróżniać niektóre z nich, jako mające szczególne znaczenie dla ustroju państwa. Normy takie określane są, zależnie od autorstwa opracowania, jako „zasady naczelne konstytucji”, „zasady konstytucyjne”, „zasady prawa konstytucyjnego”, „konstytucyjne zasady ustroju”, „zasady ustrojowe” lub „konstytucyjne zasady prawa”. Niezależnie jednak od nazwy nadanej im przez autora opracowania są one przede wszystkim zasadami prawa i jako takie należy je postrzegać. Głównym wyróżnikiem zasady prawa musi być jej szczególna doniosłość dla systemu prawa bądź dla gałęzi prawa. Jest to cecha o znaczeniu podstawowym, bez spełnienia której norma nie może być uznana za zasadę. Zastosowanie tego kryterium pozwala na wskazanie norm zasługujących na określenie ich mianem zasad prawa. Since the structural transformation (1989-1992) authors still mention the same supreme principles, although a new constitution was resolved in 1997. It seems unlikely that coming into force of the constitution- which differs from the preceding constitutional regulations - has not caused at least minimal changes among constitutional rules of law. The paper focuses on considering if a rule stated in the 38th article of the polish constitution is a nile of law. The above regulation providing protection of life, introduced to the polish legał system by the new constitution, has never been similarly analysed.Article 38 is not only a declaration but also has a practical meaning for proclaiming and applying the law. The regulation directs the polish legał system at human protection. Ultimately, then, article 38 is a significant constitutional rule. According to the doctrine of constitutional law, such rules are defined as constitutional rules of law.The above rule should be reckoned among substantive rules as it is highly abstract and has a key meaning for the human protection provided by the constitution. This leads to the conclusion that article 38 is essential for determining main objects of the state’s activities in terms of a life protection. To sum up, it plays an important role in the polish legał system.